2021
DOI: 10.3390/ijms222313120
|View full text |Cite
|
Sign up to set email alerts
|

Designing Cardiovascular Implants Taking in View the Endothelial Basement Membrane

Abstract: Insufficient endothelialization of cardiovascular grafts is a major hurdle in vascular surgery and regenerative medicine, bearing a risk for early graft thrombosis. Neither of the numerous strategies pursued to solve these problems were conclusive. Endothelialization is regulated by the endothelial basement membrane (EBM), a highly specialized part of the vascular extracellular matrix. Thus, a detailed understanding of the structure–function interrelations of the EBM components is fundamental for designing bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 122 publications
(141 reference statements)
1
7
0
Order By: Relevance
“…2 ). These findings are in accordance with the current understanding of endothelial basement membrane biology [ 39 , 40 ], adding further support to the emergent role for mural cells in its assembly [41] .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…2 ). These findings are in accordance with the current understanding of endothelial basement membrane biology [ 39 , 40 ], adding further support to the emergent role for mural cells in its assembly [41] .…”
Section: Discussionsupporting
confidence: 90%
“…Matrigel®, Corning and Cultrex TM , Bio-Techne) reflects that of the endothelial basement membrane, which normally separates ECs from underlying mural cells (i.e. pericytes and vascular smooth muscle cells) [ 39 , 40 ]. Accordingly, the self-assembly of ASCs in gelled basement membrane extract may in fact be a manifestation of their perivascular phenotype, recapitulating their predisposition to assume an abluminal localization to the endothelial basement membrane.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, we did not detect KANK4 expression in commercially acquired HUAECs and human aorta ECs (Figure S7B) because those cells were expanded for several passages before cryopreservation and shipping. However, a previous study demonstrated that cultured HUVECs and HUAECs behave similarly regarding cell proliferation, metabolic activity, ECM production, and other cardiovascular-associated functions 43 and the quick loss of KANK4 expression in ECs after isolation. Therefore, we investigated KANK4 function in vitro by directly overexpressing KANK4 in HUVECs.…”
Section: Kank4 Promotes Vessel Enlargement In Vitromentioning
confidence: 93%